Fungsi Anggaran sebagai Pengendalian Manajemen terhadap Efisiensi Pusat-pusat Laba - Martono, C. (Jurnal Widya Manajemen & Akuntansi, 2002)
Management control system is a process that enables interaction between manager and staff that involve formal communication and non formal communication. It can endorse the efficiency of profit center. Profit center is a value of efficiency. A Profit center can be efficient among other if it uses the same input but produce more output. Control system can make for profit center with establish a standard that in the form of budget. Comparing between actual and standard (budget) can be result corrective action or feed back caused by positive deviation.